Implementasi Mesin Pengeruk Isi Buah Markisa berbasis Mikrokontroler dan Elektro Pneumatik - Sidehabi, Sitti Wetenriajeng; Akbar, Zainal; Habibuddin, Julianti; Ramadhan, Muh. Alamsyah (Jurnal Otomasi Kontrol dan Instrumentasi, 2023)
Passion fruit has a distinctive sweet and sour taste, which is quite popular in Indonesia, especially in South Sulawesi. Passion fruit is processed into syrup, and dodol is one of the typical souvenirs popular with tourists. Processing passion fruit syrup in the Micro, Small, and Medium Enterprises (MSMEs) Industry still uses very simple equipment. Hence, the quality and quantity of the product produced are not optimal. Passion fruit cutting uses a knife with a low capacity for cutting and shrinkage results, so this research aims to design a passion fruit-filled shaver machine based on a microcontroller and electro-pneumatics. This passion fruit shaver machine uses a microcontroller as the control center. First, the passion fruit passes through an infrared sensor, which detects the fruit and counts the number of incoming fruits. After that, Arduino Uno reads and activates the control relay from the DC motor. After 0.5 seconds, cylinder 1 is active, which pushes the DC motor down so that the passion fruit shrinks for 3 seconds. Then, the pneumatic push up to the normal position; after 0.5 seconds, the second cylinder actively pushes the passion fruit skin that has been shaved out (thrown away). This processes for 1 second and returns to its normal position. If there is passion fruit, it comes in again, and the tool functions similarly, and so on. The results of this study produced a passion fruit shrinker machine with dimensions of length 300 mm x width 300 mm x height 600 mm, a motor power of 240 Watt or 0.321 HP, and a production capacity of 54 kg/hour.